The Railway and Petroleum Policies of the Great Powers in the Middle East - İsmail Görgen (Avrasya İncelemeleri Dergisi)
The Middle East is the focus of attention for many states and nations due to its geographical location and has hosted numerous civilizations throughout history. In addition to being located at a crossroads, the region’s rich petroleum fields have heightened the interest in the Middle East. The mechanization and mass production that started with the Industrial Revolution also increased theneed for raw materials, which caused the great powers to engage in the agony of colonialism. Colonial states saw the Middle East as a source of raw materials for the products they would produce and as a marketplace for the surplus goods they produced. These states attempted to obtain railway concessions in the Middle East in order to increase their influence in the region. England, France, Germany, and America tried to penetrate the region economically, politically, and militarily by establishing a railway network in the Middle East, which was under the rule of the Ottoman Empire. Imperialist states began to increase their investments and concessions in the Middle East through the use of petroleum in engines and machinery. Thus, every railway began being considered as a tool for exploiting the region’s resources, especially petroleum. The struggle regarding interests in the region intensified with the outbreak of World War I. This study benefited from the use of archival documents, memoires, official correspondence, and copyrighted works in its preparation. The present study includes a literature review, classification, analysis, criticism, and synthesis stages, which are the methods for studying history. This study attempts to reveal all aspects of the railroad and petroleum struggles in the Middle East that were experienced during this historical process.